Dari Ladang ke Meja Makan : Kajian Etnobotani Tumbuhan Pangan Lokal di Desa Gunungronggo Kabupaten Malang - Ananda Rifta Anastasya; Rindang Sike Nurindra Jati; Fahrul Ghani Muhaimin; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Susriyati Mahanal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Local food plants play an important role in supporting food security and the sustainable utilization of biological resources at the community level. However, information regarding the types and utilization patterns based on local knowledge is still limited, particularly in Gunungronggo Village. This study aims to identify the types of local food plants and analyze their utilization patterns using an ethnobotanical approach. The method used was a mixed-method (qualitative–quantitative) with an exploratory sequential design. Qualitative data were obtained through interviews with informants selected using purposive and snowball sampling techniques, while quantitative data were collected from 92 respondents through questionnaires. The results showed that there were 24 species of food plants utilized, consisting of various growth forms dominated by herbs, trees, lianas, and shrubs. The highest Informant Consensus Factor (ICF) value of 0.99 indicates a strong agreement among the community regarding the use of plants as sources of carbohydrates and vegetables. The Relative Frequency of Citation (RFC) showed the highest value of 1 for Colocasia esculenta, Oryza sativa, Zea mays, Musa sp., Carica papaya, Ipomoea aquatica, Ipomoea batatas, and Capsicum annuum. The highest Species Use Value (SUV) was found in Musa sp. with a value of 2.54. The family Musaceae had the highest Family Use Value (FUV) of 2.54, while the most utilized plant part was fruit (60.4%). The highest Fidelity Level (FL) value was found in Carica papaya, Durio zibethinus, Persea americana, Selenicereus undatus, Lansium domesticum, and Psidium guajava (100%), indicating high specificity of use. This study concludes that the utilization of local food plants in Gunungronggo Village is diverse, structured, and supported by strong local knowledge.